Determinantes de largo plazo de la participación del sector informal en la PEA - Céspedes Murga, Sebastián (Pontificia Universidad Católica del Perú, 2022)
The high participation of the informal sector in the economically active population (EAP) represents a key problem for the Peruvian economy, particularly in its condition as a developing country. In this sense, the aim of this thesis is to identify the long-term determinants of informal sector participation in the EAP. This study is related to the so-called “dual vision of informality”, to which LaPorta and Shleifer (2014) have recently contributed. Our hypothesis states that when both the per-capita capital stock and productivity rates of growth slow down below the population rate of growth, participation of the informal sector in the EAP tends to grow. That is to say, in the long-term participation of the informal sector in the EAP is determined by this set of variables. This hypothesis relies on an assumption made on the basis of Keynesian growth theory, by Thirlwall (2007) and Jiménez (2011), which consists of the fact that developing economies exhibit a warranted rate of growth which is inferior to its natural rate of growth. This causes a long-term increasing unemployment growth pattern. In other words, we hold that a high participation of the informal sector in the EAP is a byproduct of this growth pattern. In order to test this hypothesis a basic cointegration model will be applied. This will allow us to test the existence of long-term relationships between the rate of growth of informal sector participation in the EAP and the productivity, per-capita capital stock and population rates of growth with data from Peru between 1950 and 2015. A preliminary data analysis shows that, between the decades of the 1970s and 1990s, both productivity and per-capita growth did slow down below population growth, which could explain a positive growth in informal sector participation in the EAP during those years.
Keywords: Población activa--Perú; Sector informal--Perú; https://purl.org/pe-repo/ocde/ford#5.02.01